CuBr2-Promoted Tetrahydrofuranylation of Alcohols and 1,3-Dione - Wang, Meng-Ke; Zhou, Zeng-le; Tang, Ri-Yuan; Zhang, Xing-Guo; Deng, Chen-liang (Synlett, 2013)
A method for the CuBr2-promoted tetrahydrofuranylation of alcohols and 1,3-dione has been developed. A variety of different alcohols were efficiently converted into the corresponding 2-tetrahydrofuran ethers in the presence of CuBr2. It is noteworthy that this protocol also successfully converted 1,3-diphenyl-1,3-dione into the corresponding 2-tetrahydrofuran derivative in good yield.
Keywords: copper; protecting groups; alcohols; diones; ethers